Intertextual Awareness in EFL Report Writing: A Comparison of Field- and Web-Based Source Use - Amroh Umaemah; Hendi Hidayat; Tedi Rohadi (MASI Mandiri Edukasi, 2026)
This qualitative study explores how EFL students interactively work with field- and web-based sources in academic report writing through processes of selection, interpretation, and integration. Data were collected through semi-structured reflective questionnaires, semi-structured interviews, and student report texts involving 32 third-semester students. Grounded in Bazerman’s intertextual typology and Canagarajah’s translingual framework, thematic analysis identified two overlapping intertextual repertoires that reflected distinct patterns of meaning-making. Field-based engagement encouraged experiential curiosity, dialogic interpretation, and narrative integration, in which students drew on cultural immediacy and personal experience to construct a stronger authorial voice and epistemic agency. In contrast, web-based engagement was more strongly associated with algorithmic search behaviour, multimodal decoding, and citation-oriented structuring. Although both source types supported strategic meaning-making, field-based practices demonstrated deeper interpretive engagement and more independent knowledge construction. The findings indicate that pedagogical support should integrate embodied inquiry and digital literacy to strengthen students’ critical intertextual competence in academic writing. The study also suggests incorporating hybrid source use into EFL writing instruction to support more balanced and adaptive academic authorship.